CCR5 Inhibition Prevents Cardiac Dysfunction in the SIV/Macaque Model of HIV. Issue 2 (2nd April 2014) - Kelly, Kathleen M.; Tocchetti, Carlo G.; Lyashkov, Alexey; Tarwater, Patrick M.; Bedja, Djahida; Graham, David R.; Beck, Sarah E.; Metcalf Pate, Kelly A.; Queen, Suzanne E.; Adams, Robert J.; Paolocci, Nazareno; Mankowski, Joseph L.
Abstract : Background: Diastolic dysfunction is a highly prevalent cardiac abnormality in asymptomatic as well as ART‐treated human immunodeficiency virus (HIV) patients. Although the mechanisms underlying depressed cardiac function remain obscure, diastolic dysfunction in SIV‐infected rhesus macaques is highly correlated with myocardial viral load. As cardiomyocytes are not productively infected, damage may be an indirect process attributable to a combination of pro‐inflammatory mediators and viral proteins. Methods and Results: Given the diverse roles of CCR5 in mediating recruitment of leukocytes to inflammatory sites and serving as a receptor for HIV entry into cells, we investigated the role of CCR5 in the SIV/macaque model of diastolic dysfunction. We found that in SIV‐infected macaques, CCR5 inhibition dramatically impacted myocardial viral load measured by qRT‐PCR and prevented diastolic dysfunction measured by echocardiography. Complementary in vitro experiments using fluorescence microscopy showed that CCR5 ligands impaired contractile function of isolated cardiomyocytes, thus identifying CCR5 signaling as a novel mediator of impaired cardiac mechanical function. Conclusions: Together, these findings incriminate SIV/HIV gp120‐CCR5 as well as chemokine‐CCR5 interactions in HIV‐associated cardiac dysfunction. These findings also have important implications for the treatment of HIV‐infected individuals: in addition to antiviral properties and reduced chemokine‐mediated recruitment and activation of inflammatory cells, CCR5 inhibition may provide a cardioprotective benefit by preventing cardiomyocyte CCR5 signaling.